2007
DOI: 10.1186/1471-2164-8-93
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of insect-specific proteins by genome data analysis

Abstract: Background: Insects constitute the vast majority of known species with their importance including biodiversity, agricultural, and human health concerns. It is likely that the successful adaptation of the Insecta clade depends on specific components in its proteome that give rise to specialized features. However, proteome determination is an intensive undertaking. Here we present results from a computational method that uses genome analysis to characterize insect and eukaryote proteomes as an approximation comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
37
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 46 publications
7
37
0
Order By: Relevance
“…The K a /K s ratio for SUUR orthologs varies from 0.16 to 0.23 within species from the melanogaster subgroup. The K a /K s ratio between D. melanogaster and D. yakuba orthologs is 0.16, suggesting that about one-half of the 1850 Drosophila-specific proteins evolve under stronger selection pressure than SUUR, judging from recent genomewide analysis of the Drosophila proteome (Zhang et al 2007). The same study demonstrated that proteins with orthologs in distant species tend to evolve under stronger selection pressure than Drosophilaspecific proteins.…”
Section: à6supporting
confidence: 51%
“…The K a /K s ratio for SUUR orthologs varies from 0.16 to 0.23 within species from the melanogaster subgroup. The K a /K s ratio between D. melanogaster and D. yakuba orthologs is 0.16, suggesting that about one-half of the 1850 Drosophila-specific proteins evolve under stronger selection pressure than SUUR, judging from recent genomewide analysis of the Drosophila proteome (Zhang et al 2007). The same study demonstrated that proteins with orthologs in distant species tend to evolve under stronger selection pressure than Drosophilaspecific proteins.…”
Section: à6supporting
confidence: 51%
“…These include compounds such as juvenile hormone analogs and chitin synthesis inhibitors, processes that have been studied well in Drosophila (De Loof 2008;Moussian 2012). Considering that some fraction of nonconserved genes are also essential for viability in Drosophila (Yamamoto et al 2014a) and that specific nonessential genes are often involved in fitness (Zhang et al 2007), studies of Drosophila genes that do not have obvious direct human homologs remain important.…”
Section: Revealing Hidden Homologies Through Experimental Approachesmentioning
confidence: 99%
“…In order to consider these approaches, we can look at the fly genome as containing two types of genes: those with sequence homology with human genes and those that have no obvious human homologs. Of course, many of the fly genes that have no obvious human homologs are conserved in other phyla and the number of truly specific Drosophila melanogaster genes is very limited (Zhang et al 2007).…”
Section: A Comparison Of Drosophila and Human Genomesmentioning
confidence: 99%
“…1) based on a homologue search using BLAST [21] with an e-value cutoff of 10 −5 [5,[12][13][14] and scoring matrices of Blossum62, Pam70, and Pam30. As the proteins are of different sizes and scored by different matrices, we divided 26,150 C. elegans proteins into three sets: a set of proteins that are less than 30 aa in length, a set between 30 and 70 aa, and a set more than 70 aa, for BLASTP analyses.…”
Section: Homologue Searchmentioning
confidence: 99%
“…However, study of these genes is helpful to aid in the comprehensive understanding of a species. With the increasing development of sequencing technologies, we have gained access to a number of genomes and transcriptomes from a wide range of species, which has aided the extensive study of the LSGs within mammals [8][9][10], insects [2,11,12], fish [13], plants [5,[14][15][16], and microbial species [17][18][19][20]. However, the LSGs in C. elegans have not yet been researched through genomewide methods.…”
Section: Introductionmentioning
confidence: 99%